Neurogenic Thoracic Outlet Syndrome: Comparison of early Versus late Surgical Intervention in terms of Improvement in Clinical Symptoms - Ali Raza, Muneeb Ur Rehman Niazi, Abdulqadir, Riaz Qadeer Niazi, Shoaib Anwar, Syed Hyder Raza (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Neurogenic thoracic outlet syndrome is a condition with unpredictable response to conservative management, and the optimal timing of surgical intervention remains debated. Objectives: To determine the impact of surgical intervention on clinical, electrophysiological, and functional outcomes in patients with neurogenic thoracic outlet syndrome in Pakistan. Methods: This was a prospective study which included diagnosed patients of neurogenic thoracic outlet syndrome with surgical treatment and were followed for six months postoperatively. Patients were divided into two groups based on timing of surgery, i.e. delayed surgery after failure of conservative management and early surgery following diagnosis. Preoperative assessment included clinical evaluation of patients, electrophysiological studies, and functional disability assessment using the Disability of the Arm, Shoulder, and Hand questionnaire. Postoperative outcomes were determined by using the same parameters to compare recovery between two groups of patients. Results: Radiological findings highlighted 75% of respondents with cervical rib, 15% with elongated C7 transverse process, and 10% with anomalous first thoracic rib . Preoperatively, 90% of respondents had paraesthesia and 85% had pain, with greater functional impairment and electrophysiological abnormalities observed in patients undergoing delayed surgery (Group I) compared to early surgery (Group II). Postoperatively, both groups showed improvement; significant functional recovery was observed only in the early surgery group (Group II: 27.3 ± 10.5 preoperative vs. 10.5 ± 5.7 postoperative, p < 0.001); whereas the improvement in delayed surgery patients was not statistically significant (Group I: 34.2 ± 13.3 vs. 23.5 ± 13.9, P = 0.07). Conclusion: Surgical decompression is an effective treatment for neurogenic thoracic outlet syndrome; however, early surgical intervention yields superior clinical and functional outcomes compared with delayed treatment. Keywords: Neurogenic thoracic outlet syndrome, Surgical decompression, Timing of surgery, Functional outcome, Electrophysiological studies, DASH score